PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI MELALUI KEPUASAN KERJA - Oey Hannes Widjaya; Herlina Budiono; Ananda Elang Putra Bayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Organizational commitment is a factor that encourages an employee to stay in a company. Organizational commitment itself can be influenced by various factors, one of which is job satisfaction. Employees with high levels of job satisfaction tend to stay in the organization where they work. Job satisfaction itself can be influenced by compensation and work environment. Providing fair compensation and according to employee expectations will increase job satisfaction which will have an impact on increasing organizational commitment as well as the work environment. A comfortable work environment that can support employees' work can make employees feel satisfied which ultimately makes employees want to stay in the organization. The purpose of this study was to determine the effect of compensation and work environment on organizational commitment through job satisfaction. Researchers distributed questionnaires to 96 respondents. The sampling method is non-probability sampling with the type of snowball sampling. The data analysis method in this research is quantitative method and Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach. The results of this study state that compensation and work environment have an effect on job satisfaction while compensation and work environment have no effect on organizational commitment and job satisfaction has an effect on organizational commitment to employees of PT